ANALISIS PERBANDINGAN PREDIKSI KONDISI FINANCIAL DISTRESS DENGAN MENGGUNAKAN METODE ALTMAN, SPRINGATE, DAN ZMIJEWSKI - Fitri Listyarini (Jurnal Bina Akuntansi, 2020)
This study aims to: 1) Determine the accuracy of the Altman model, the springate model and the zmijewski model in predicting financial distress conditions in manufacturing companies in Indonesia, 2) To find out the most accurate prediction models in predicting financial distress conditions in manufacturing companies in Indonesia. This study compares three financial distress prediction models, the Altman, Springate and Zmijewski models. The population of this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange for the period 2011-2014. The sampling technique is pair matching sampling with a total sample of 28 companies, consisting of 14 companies experiencing financial distress and 14 companies not experiencing financial distress. Comparisons of the three financial distress prediction models are made by analyzing the accuracy of each model based on the company's real conditions. The results show that the zmijewski model is the most accurate model for predicting financial distress in manufacturing companies in Indonesia because it has the highest level of accuracy compared to other models, which is 100%, followed by the Springate model which has an accuracy rate of 89.29% and the Altman model by 75%.